Ovarian Vein Thrombosis Complicated by Pulmonary Embolism after Cesarean Delivery in the Presence of a Large Fibroid: Case Report and Literature Review of Contributing Factors - Elie S. Finianos; Stephanie F. Yacoub; Mary F. Chammas (Hindawi Limited, 2021)
Ovarian vein thrombophlebitis is rare and mostly occurs during the puerperal period and in higher rates after a cesarean delivery. The objective of this case report and literature review is to highlight the rare occurrence of an ovarian vein thrombosis in a 37-year-old woman postcesarean delivery in the setting of a large uterine fibroid who subsequently developed a pulmonary embolism. The patient presented with severe abdominal pain, fever, and chills. Imaging showed a right ovarian vein thrombosis. Following initiation of anticoagulation therapy, she developed dyspnea and testing showed a subsegmental pulmonary embolism. Further investigation showed that the patient had an undiagnosed thrombophilia thus meeting the classic Virchow triad. Complete clinical recovery was observed, and anticoagulation therapy was continued for 1 year. Our case highlights the importance of recognizing ovarian vein thrombosis because of the risk of fatal complications such as pulmonary embolus. The presence of large fibroids should raise our awareness for OVT in the setting of abdominal pain and fever. The absence of complications in previous pregnancies should not alter our clinical suspicion.